Mechanism of aspirin-induced inhibition on the secondary hyperalgesia in osteoarthritis model rats. Issue 5 (May 2020) - Niibori, Mizuho; Kudo, Yasushi; Hayakawa, Takuya; Ikoma-Seki, Keiko; Kawamata, Ryosuke; Sato, Atsushi; Mizumura, Kazue
Abstract: Aims: The daily activity of osteoarthritis (OA) patients is limited by chronic pain and central sensitization. Although non-steroidal anti-inflammatory drugs (NSAIDs) and acetaminophen are the first-line drugs for the treatment of OA-related pain, their efficacy on central sensitization remains unclear. In the present study, we evaluated the effect of acetylsalicylic acid (ASA, Aspirin) using an OA model induced by monosodium iodoacetate (MIA), which has a similar disease progression to human OA. Main methods: Secondary hyperalgesia was assessed at the plantar surface of the hind paw by Von Frey test. We evaluated the expression of acid-sensing ion channel 3 (ASIC3) in dorsal root ganglia and that of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) in the spinal cord, which may cause secondary hyperalgesia in OA, by immunohistochemical analysis and real-time qPCR. Key findings: The administration of ASA attenuated secondary hyperalgesia at 1–3 weeks after MIA, while celecoxib, a selective cyclooxygenase (COX)-2 inhibitor, failed to attenuate secondary hyperalgesia at week 2 after MIA injection, suggesting that ASA exerts its analgesic effect through a COX-2-independent pathway. Immunohistochemical analysis of the dorsal root ganglia indicated that ASA reduced the expression of ASIC3 during OA progression. Expression of TNF-α mRNA, but not IL-1β mRNA, in the spinal cord following MIA injection was suppressed by ASA administration. Significance: These findings suggest that ASA may have the ability to attenuate secondary hyperalgesia through suppression of ASIC3 and/or TNF-α expression. ASA is therefore a clinically useful analgesic drug for treatment of secondary hyperalgesia in OA. Abstract : Osteoarthritis; Acetylsalicylic acid; Secondary hyperalgesia; Monosodium iodoacetate; Rat model; Immunology; Pharmaceutical science; Pain research; Pharmacology